Suppressing NK Cells by Astragaloside IV Protects Against Acute Ischemic Stroke in Mice Via Inhibiting STAT3 - Li, Shichun; Dou, Baokai; Shu, Shi; Wei, Luyao; Zhu, Shiguo; Ke, Zunji; Wang, Zhifei (Frontiers in Pharmacology, 2022)
Natural killer (NK) cells, a key member of innate lymphocytes, are a promising immunotherapeutic target for ischemic stroke. Astragaloside IV (ASIV) is isolated from Astragalus membranaceus, a herbal medicine possessing immunomodulatory ability. This study investigated the effect of ASIV on NK cells during the acute stage of brain ischemic injury in a mouse model of middle cerebral artery occlusion (MCAO). MCAO mice treated with ASIV had better functional outcomes, smaller brain infarction and less NK cell brain infiltration. NK cell depletion echoed the protective effect of ASIV. Notably, ASIV did not enhance the protective effect of NK cell depletion against brain ischemic injury. ASIV inhibited glial cell-derived CCL2-mediated chemotaxis to prevent post-ischemic NK cell brain recruitment. Meanwhile, ASIV also abrogated NK cell-mediated cytolytic killing of neurons subjected to oxygen-glucose deprivation and suppressed NK cell-derived IFN-gamma and NKG2D expression in the ischemic brain. The inhibitory effect of ASIV on NK cell brain infiltration and activation was mimicked by cryptotanshinone, a STAT3 inhibitor. There was no additive effect when ASIV and cryptotanshinone were used together. In conclusion, ASIV inhibits post-ischemic brain infiltration and activation of NK cells through STAT3 suppression, and this inhibitory effect of ASIV on NK cells plays a key role in its protection against acute ischemic brain injury. Our findings suggest that ASIV is a promising therapeutic candidate in NK cell-based immunotherapy for the treatment of acute ischemic stroke and pave the way for potential clinical trials.